The Principle Of Strict Liability In Legal Responsibility For Environmental Pollution: A Conceptual Analysis - Hanum, Paujiah; Ika Pratiwi, Rani; Doly Indra Utama, Iqbal; Muslim, Yasir; Ismelina Farma Rahayu, Mella (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
The principle of strict liability is a legal concept that emphasizes absolute responsibility without the need to prove the element of fault. In the context of environmental law, this principle has an important position as the basis for law enforcement against perpetrators of environmental pollution and destruction. This article aims to conduct a conceptual study of the application of the principle of strict liability in the Indonesian environmental law system, especially within the framework of Law Number 32 of 2009 concerning Environmental Protection and Management (UU PPLH). Through a normative approach, this article analyzes the philosophical, legal, and practical basis of the principle and identifies challenges in its implementation. This study concludes that the principle of strict liability is an important instrument but faces obstacles in the practice of environmental law enforcement in Indonesia.